Profile of STING agonist and inhibitor research: a bibliometric analysis - Wang, Xuemei; Wang, Qian; Gao, Yidan; Jiang, Lijuan; Tang, Lingli (Frontiers in Pharmacology, 2025)
BackgroundSTING is a core signaling hub molecule in the innate immune system, involved in various diseases, including infectious diseases, autoimmune diseases, tumors, aging, organ fibrosis, and neurodegenerative diseases. Its activation has shown great potential in anti-tumor and anti-infective therapies, with STING agonists emerging as a promising approach in cancer immunotherapy in recent years. This study identifies research trends and potential directions in the field by collecting and analyzing relevant literature.MethodsA total of 527 publications regarding STING agonists and 107 about inhibitors were retrieved from the WOS Core Collection database. Bibliometric information was extracted with CiteSpace and VOSviewer software for visualization.ResultsIt shows that research on both STING agonists and inhibitors is burgeoning rapidly. The United States and China are leading contributors in this field. Application of STING agonists primarily focuses on cancer immunotherapy, while STING inhibitors target inflammation, particularly neuroinflammation and acute lung injury.ConclusionCurrent research emphasizes optimizing STING agonists for permeability, efficacy, and safety, with nanotechnology and lipid nanoparticles being prominent delivery techniques. Future research is expected to focus on drug development and clinical applications. This comprehensive bibliometric analysis provides clinical insights and a guide for further investigation to STING agonist/inhibitor.